JURNAL REVIEW: PERBANDINGAN SISTEM OPERASI LINUX DENGAN SISTEM OPERASI WINDOWS - Imam Yunianto; Krisna Adhiyarta (Institut Bisnis Muhammadiyah Bekasi, 2020)
Operating Systems are four components that must not be absent for Information Systems. For companies that have implemented a computerized system as part of the company's operational support, must pay attention to what Operating Systems are good for the company. Including the advantages and company budget for Information Technology. To get a good Operating System in accordance with office needs, a comparison of the Windows Operating System and Linux Operating System. The results of the comparison of these two Operating Systems can be input for deciding which Operating System is suitable for the company.